2022
DOI: 10.1186/s12885-021-09160-1
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome deep sequencing analysis of cell-free DNA in samples with low tumour content

Abstract: Background Circulating cell-free DNA (cfDNA) in the plasma of cancer patients contains cell-free tumour DNA (ctDNA) derived from tumour cells and it has been widely recognized as a non-invasive source of tumour DNA for diagnosis and prognosis of cancer. Molecular profiling of ctDNA is often performed using targeted sequencing or low-coverage whole genome sequencing (WGS) to identify tumour specific somatic mutations or somatic copy number aberrations (sCNAs). However, these approaches cannot ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…provide evidence that ctDNA is enriched within the dinucleosome fraction in early- and late-stage tumors, respectively. 27 , 28 Ganesamoorthy et al. investigated plasma samples with low tumor content and did not detect enrichment in cfDNA fragments <150 bp, but reported significant enrichment of tumor-derived fragments within the dinucleosome fraction.…”
Section: Discussionmentioning
confidence: 99%
“…provide evidence that ctDNA is enriched within the dinucleosome fraction in early- and late-stage tumors, respectively. 27 , 28 Ganesamoorthy et al. investigated plasma samples with low tumor content and did not detect enrichment in cfDNA fragments <150 bp, but reported significant enrichment of tumor-derived fragments within the dinucleosome fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed higher fragmentation of tumor-derived cfDNA fragments and their enrichment with somatic mutations, particularly in colorectal cancer patients (Diehl et al, 2005;Mouliere et al, 2011;2013), while at the same time some evidence conversely support the presence of longer molecules in tumor cfDNA fraction (Umetani et al, 2006;Ganesamoorthy et al, 2022). The complexity of cfDNA size profile seems to be the result of a balance between several biological processes including apoptosis, necrosis, senescence and active release that may be altered in pathology (Rostami et al, 2020;Ungerer et al, 2021;Ungerer et al, 2022).…”
Section: Cell-free Dna Contamination Screeningmentioning
confidence: 95%
“…Interestingly, 90% of somatic cfDNA alterations were not detected in matched tumor tissues and were due to two background mutational signatures. Intriguingly, cfDNA fragments ranging from 300 bp to 350 bp in size (e.g., di-nucleosomal plasma DNA) had a much higher proportion (30%) of mutations in common with the tumor [ 43 ]. The findings of this study show the complexity of ctDNA analysis using WGS.…”
Section: Methods For the Detection Of Circulating Tumor Dnamentioning
confidence: 99%